2009
DOI: 10.1182/blood-2008-08-174128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of decreased free protein S levels: results from a retrospective family cohort study involving 1143 relatives

Abstract: Conflicting data have been reported on the risk for venous thrombosis in subjects with low free protein S levels. We performed a post-hoc analysis in a singlecenter retrospective thrombophilic family cohort, to define the optimal free protein S level that can identify subjects at risk for venous thrombosis. Relatives (1143) were analyzed. Relatives with venous thrombosis (mean age 39 years) had lower free protein S levels than relatives without venous thrombosis (P < .001), which was most pronounced in the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
3
44
1
1
Order By: Relevance
“…Protein S type III deficiency was separately analyzed in a previous article of ours, where it showed to be an independent risk factor for venous thrombosis when free protein S levels were much lower than the lower limit of the normal range. 18 Protein C deficiency type I and type II were defined by decreased levels or activity of protein C antigen (both Ͻ 65 IU/dL). Deficiencies were considered inherited if they were confirmed by measuring a second sample that was collected 3 months later and were found in at least 2 family members.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Protein S type III deficiency was separately analyzed in a previous article of ours, where it showed to be an independent risk factor for venous thrombosis when free protein S levels were much lower than the lower limit of the normal range. 18 Protein C deficiency type I and type II were defined by decreased levels or activity of protein C antigen (both Ͻ 65 IU/dL). Deficiencies were considered inherited if they were confirmed by measuring a second sample that was collected 3 months later and were found in at least 2 family members.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…12 Such complex and elusive mechanisms could explain why, despite the key role of PS in the regulation of thrombin generation, its involvement in the susceptibility of venous thrombosis (VT) remains obscure. Although PS deficiency is considered a risk factor for VT, [13][14][15] total PS and fPS show very little correlation with VT. 16,17 C4BP is a large plasma protein existing in 3 different isoforms, ␣ 7 ␤ 1 , ␣ 7 ␤ 0 , and ␣ 6 ␤ 1 , according to the number of identical ␣-chains (6 or 7) and the presence/absence of a single ␤-chain. 18 The main isoform is ␣ 7 ␤ 1 , whereas the ␣ 7 ␤ 0 isoform lacking the ␤-chain represents approximately 17% of the C4BP molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of heterozygous ProS deficiency is 2-8% in thrombosis patients in Caucasian populations [15], whereas the prevalence in the general population is estimated to be 0.03-0.13% in Caucasians and 0.06-1.12% in Southeast Asians [16][17][18]. Familial and case-control studies suggest that PSD is associated with a 2.5-to 11-fold increased risk of venous thrombosis [15,19,20]. In addition to congenital deficiency, there are a number of physiologic and pathologic conditions that lead to decreased plasma ProS levels such as oral contraceptives, pregnancy, hormone-replacement therapy, and hepatic disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports have suggested that Type I and Type III are actually two phenotypes of the same genetic defect [23,24]. In addition, several studies suggest that the partial effect of missense mutations could correlate well with the phenotype of ProS deficiency [15,20,[25][26][27]. Plasma protein S parameters (activity and free ProS level) depend on the nature of the missense mutations and the secretion differences.…”
Section: Introductionmentioning
confidence: 99%